The Representation of Character Education on Teachers’ Utterances in Early Childhood Learning - Noor Eka Chandra; Imam Suyitno (Jurusan Sastra Indonesia, 2017)
The purposes of the study were to determine the forms of teachers’ utterances and the forms of teachers’ speech techniques that represent character education in early childhood learning. The data was collected by conducting observation, recording, and interviews. The sources of the research data were four teachers who taught in the fourth grade, namely SDN Kebun Bunga 1 and SDIT Ukhuwah. The results showed that the teachers’ utterances which represent character education in early childhood learning appeared in various forms of utterances and speech techniques in accordance with the context of the situation said. First, the forms of utterance that represent character education in teaching was realized through the use of dictions and the form of speech presentation. The dictions usage includes the use of the modality, the use of pronouns, the use of adjectives, and the use of verbs. In the form of the teachers’ speech presentation, it included direct and indirect speech presentation. Second, the speech development techniques included repetition technique, explanation technique, and detailed technique. The character educations represented through teachers’ utterance were the character of religion, discipline, hard work, responsibility, honesty, environment caring, national spirit, curiosity, intelligence, independency, social care, and tolerance.